Traditional Art Dance Therapy to Reduce Stress Levels of Elementary School Students - Shinta Restu Wibawa; Christantie Effendy; Heny Suseani Pangastuti; Ami Novianti Subagya; Eriyono Budi Wijoyo; Aisya Puteri Andari; Dwi Apriliana; Qurrota Aini Zahrotu Sholikhah (Fakultas Ilmu Keperawatan Universitas Indonesia, 2024)
COVID-19 pandemic has accelerated the development of new learning systems that are more student-centered. Unfortunately, elementary school students experienced stress and difficulties in adapting from face-to-face to online learning system. Online learning environment lacks in accommodating outdoor activities which are important for children. Several techniques can be applied to reduce stress, including dancing. This research aimed to examine the effectiveness of Traditional Art dance Therapy (TATA) for elementary school students in reducing stress. In this quasi-experimental research, one-group pretest-posttest design without control group was applied, involving 84 students at one elementary school in Yogyakarta, Indonesia. Students’ levels of stress were measured using the school-based stressors scale and were analyzed using bivariate Wilcoxon test. The results of the data analysis showed that older students had relatively lower stress levels than younger ones. A significant decrease in stress (p < 0.001) from 61.90 to 41.99 was identified between the stress levels before and after the implementation of TATA. It concludes that TATA effectively reduces the stress levels among elementary school students adapting to the new learning system in the new normal era after COVID-19 pandemic. Keywords: elementary school, stress, traditional art dance therapy Abstrak Terapi Tari Seni Tradisional (TATA) untuk Mengurangi Tingkat Stress pada Siswa Sekolah Dasar. Pandemi COVID-19 telah mempercepat pengembangan sistem pembelajaran baru yang lebih berpusat pada siswa. Sayangnya, siswa sekolah dasar mengalami stres dan kesulitan dalam beradaptasi dari sistem pembelajaran tatap muka ke sistem pembelajaran online. Lingkungan belajar online kurang mengakomodasi kegiatan di luar ruangan yang penting bagi anak-anak. Beberapa teknik dapat diterapkan untuk mengurangi stres, termasuk menari. Penelitian ini bertujuan untuk mengetahui efektivitas Terapi Tari Seni Tradisional (TATA) untuk siswa sekolah dasar dalam mengurangi stres. Penelitian ini merupakan penelitian quasi-experimental dengan desain pretest-posttest satu kelompok tanpa control grup. Delapan puluh empat siswa di salah satu sekolah dasar di Yogyakarta, Indonesia, berpartisipasi dalam penelitian ini. Tingkat stres diukur dengan menggunakan school-based stressors scale. Data dianalisis secara bivariate menggunakan uji Wilcoxon. Siswa yang berusia lebih tua dilaporkan memiliki tingkat stres yang relatif lebih rendah dibandingkan siswa yang berusia lebih muda. Terdapat penurunan stress yang signifikan (p < 0,001) antara tingkat stres pada siswa sebelum dan sesudah terapi tari seni tradisional, dengan tingkat stres dari 61,90 menjadi 41,99. Terapi tari seni tradisional (TATA) efektif menurunkan tingkat stres pada siswa sekolah dasar yang mengalami perubahan sistem pembelajaran di era new normal. Kata Kunci: sekolah dasar, stres, terapi tari seni tradisional